Pengangguran Dan Tawaran Solutif Dalam Perspektif Islam - Moh. Subhan (JES (Jurnal Ekonomi Syariah), 2018)
Indonesia has crucial economic issue that has a very negative impact on other sectors. The problem is unemployment. The unemployment is an economic problem itself. The unemployment can also be a psychological burden for those concerned as well as being a social problem with the emergence of various kinds of social diseases; criminal and immoral acts. In addition, the unemployment also has a negative impact on the decline of the aqidah and moral, households, nations and countries. From an economic standpoint, the unemployment is a major problem that weighs on the economy as a whole, because unemployment is a waste of the valuable potential of human resources that impact on the disbursement of natural resources. Where appropriate natural resources can be optimally and maximally motivated, it turns out to be wasted, because the work ethic of the community is very low. Islam as a universal religion, encourages its adherents to work by producing and pursuing economic activities in all its forms as one solution to overcome unemployment. The work recommended by Islam is to work well (ihsan) full of perseverance and professionalism. Fulfillment of basic needs is the responsibility of each individual and the state must provide facilities and infrastructure that support the implementation of this. The decision and direction of government policies have an important role in suppressing the unemployment rate. Keywords: Unemployment, Solutive Bid, Islamic Perspective